Nutritional consequences of sleep deprivation in children and adolescents: an integrative review (Research, Society and Development, 2021)
Sleep is a body’s process for metabolic and physiological regulation in all humans, becoming necessary both in it’s quantity and quality. Conduct a integrative review in order to analyze the food and the nutritional consequences in children and adolescents suffering from sleep deprivation.  A systematic search of articles indexed in the following databases was carried out: PubMed, Biblioteca Virtual da Saúde (BVS) and Web of Science published until 03/12/2020. Publications in all languages were included. Two independent reviewers selected the eligible articles and extracted data from those selected articles. Based on the 405 found, after applying the inclusion criteria, 28 articles were included. In view of the consequences of sleep deprivation, a risk factor for overweight and obesity was found, larger anthropometric measurements (waist circumference, hip circumference and body fat percentage), increase of Body Mass Index, higher caloric consumption, higher intake of processed food and lower intake of fruits. In conclusion, sleep deprivation has negative consequences for both children and adolescents, having as one of the main results the risk for overweight and obesity, higher consumption of ultra-processed foods, higher calorie intake and lower intake of fruits. Concludes Therefore, health education on this topic should be further discussed among parents and/or guardians of children and adolescents.